THE EFFECT OF THE PSYCHO-EMOTIONAL STRESS ON THE STATE OF MICROBIOTA OF THE GINGIVAL SULCUS - Marchenko, A.V.; Loban, G.A.; Petrushanko, T.O.; Chereda, V.V.; Faustova, M.O.; Ananieva, M.M. (World of Medicine and Biology, 2020)
This study aimed to investigate the effect of psycho-emotional stress on the state of microbiota of the gingival sulcus in the state of eubiosis and dysbiosis in young people. The research involved 182 students of the medical university. As a model of acute psycho-emotional stress the situation of passing an important exam was used. A microbiological examination of the total microbial population of gingival sulcus and its population of microbiota, was performed with the standard methods. The impact of the stressor on the background of imbalance of the microbial homeostasis of the tooth-gingival crevice, causes the intensification of the imbalance of microbial associations in the form of commensal microflora reduction and the increase of opportunistic microflora.
Keywords: microbiota of the gingival sulcus; eubiosis; dysbiosis; psycho-emotional stress